2021
DOI: 10.1108/jstpm-10-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of private and public investment in R&D on innovation in Mexico’s biotechnology firms

Abstract: Purpose In light of the controversy between the theoretical importance of financing biotechnology firms’ research and development (R&D), and the firms’ contradictory and ambivalent empirical results, this paper aims to contribute to the debate by providing empirical evidence from Mexico’s case. Design/methodology/approach The authors use the probit model to determine if firms’ achievements in innovations are related to both private and public financing, and if so, to calculate their marginal effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Junior et al [45] highlighted the fact that public funding played an important role in stimulating research and development activities. Oliver-Espinoza et al [46] stated that they found no relationship between public financing and the results regarding innovation. This may be an exception, since various successful policies giving rise to radical innovations have concentrated on the formation of markets through direct generalized public funding [47].…”
Section: Relationships With the State In Terms Of Innovationmentioning
confidence: 98%
“…Junior et al [45] highlighted the fact that public funding played an important role in stimulating research and development activities. Oliver-Espinoza et al [46] stated that they found no relationship between public financing and the results regarding innovation. This may be an exception, since various successful policies giving rise to radical innovations have concentrated on the formation of markets through direct generalized public funding [47].…”
Section: Relationships With the State In Terms Of Innovationmentioning
confidence: 98%
“…Prior studies have provided mixed findings. Some studies argue in favor of a positive relationship between investment in innovation activities and innovation output (Rammer & Schubert, 2018;Baumann & Kritikos, 2016;Pellegrino & Savona, 2017;Hottenrott & Richstein, 2020;Michaelis & Markham, 2017), whereas others argue that the level of innovation investment does not interfere with their results (García-Quevedo et al, 2018;Oliver-Espinoza & Stezano, 2021;Audretsch & Belitski, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…García-Quevedo et al (2018) studied only the impact of R&D investments. Oliver-Espinoza and Stezano (2021) and Audretsch and Belitski (2020) were even more restrictive and observed the impact of investment only in internal R&D.…”
Section: Introductionmentioning
confidence: 99%